Redox control and oxidative stress in yeast cells - Herrero, Enrique; Ros, Joaquim; Bellí, Gemma; Cabiscol, Elisa (Biochimica et biophysica acta, 2008)
Protein structure and function can be altered by reactive oxygen species produced either by cell metabolism or by external oxidants. Although catalases, superoxide dismutases and peroxidases contribute to maintaining non-toxic levels of reactive oxygen species, modification of amino acid side chains occurs. In particular, oxidative modification of sulphydryl groups in proteins can be a two-faceted process: it could lead to impairment of protein function or, depending on the redox state of cysteine residues, may activate specific pathways involved in regulating key cell functions. In yeast cells, the thioredoxin and glutaredoxin systems participate in such redox regulation in different cell compartments, and interplay exists between both systems. In this context, glutaredoxins with monothiol activity initially characterised in Saccharomyces cerevisiae may display specific regulatory functions at the mitochondria and nuclei. Furthermore, their structural conservation in other organisms point to a conserved important role in metal homeostasis also in higher eukaryotes. Control of gene expression in response to oxidative stress is mediated by several transcription factors, among which Yap1 has a predominant role in S. cerevisiae (Pap1 in Schizosaccharomyces pombe and Cap1 in Candida albicans). In combination with Gpx3 peroxidase and Ybp1 protein, the activity of Yap1 is itself controlled depending on the redox state of some of its cysteine residues, which determines the nucleocytoplasmic location of the Yap1 molecules.